Improvement of Eighth Grade Students’ Scientific Thinking Skills Using Multirepresentation-Based E-Module in Science Subjects: Vibrations, Waves, and Light - Dwi. F, Helmi Susanti; Mahardika, I Ketut; Wahyuni, Sri (Peneliti.net, 2024)
This study aims to explore Improvement of Eighth Grade Students' Scientific Thinking Skills Using Multirepresentation-Based E-Module in Science Subjects: Vibrations, Waves, and Light. The research design employed was the ADDIE model with five stages: analysis, design, development, implementation, and evaluation. The study sample consisted of one class, specifically Grade VIII D, which utilized multirepresentation-based e-modules in IPA, comprising 34 students (18 females and 16 males). Data collection included pre- and post-treatment assessments of conceptual mastery and application abilities using tests. Data analysis utilized the N-Gain test to compare the average score improvements before and after employing multirepresentation-based e-modules in IPA. The results indicate that the use of multirepresentation-based e-modules significantly enhances students' scientific thinking abilities in understanding concepts related to vibrations, waves, and light. These findings suggest that employing multirepresentation approaches within e-module technology can effectively enhance science learning at the middle school level.